The Population and Reproductive Health Capacity Building Program - Independent Evaluation Group (Washington, DC: World Bank, 2017)
This is the Global Program Review (GPR) of the Population and Reproductive Health Capacity Building Program (PRHCBP). Established in 1999, PRHCBP is a merger of three pre-existing programs: population and reproductive health, safe motherhood, and the program to reduce the practice of Female Genital Mutilation (FGM) and adolescent health. The main objective of the program is to build the capacity of civil society organizations to develop and implement culturally appropriate interventions in the sensitive fields of population and reproductive health, leading to healthier behavior at individual and community levels, reducing the impoverishing effects of poor reproductive health, and improving reproductive, maternal and child health outcomes of hard-to-reach populations. The review follows Independent Evaluation Group (IEG) guidelines for preparing GPRs (annex A). These guidelines were first approved in 2006, well after PRHCBP was initially conceived and implemented. As a new evaluation product of IEG, GPRs are attempting to raise the standards of the design, management, implementation and evaluation of Global and Regional Partnership Programs (GRPPs). This is an ongoing process, and programs that are reviewed are not expected to have adhered to all the standards inherent in these guidelines, which had not been established at their outset.